Vročanje redne in izredne odpovedi pogodbe o zaposlitvi - Ferlin, Katarina (Delavci in delodajalci, 2017)
The new Slovene Employment Relationship Act (ERA-1) significantly simplified the provisions relating to serving the notice of an employment contract termination. Due to these changes, the legal protections which existed within the former provisions were reduced significantly. The modified provisions have caused numerous shortcomings in practice, which were partly tackled by the Constitutional Court of the Republic of Slovenia which derogated the fourth paragraph of Article 88 of the ERA- 1. In this paper, the remaining weaknesses are discussed and potential solutions are presented.
Keywords: odpoved; pogodba o zaposlitvi; prenehanje; zaposleni